Deciphering the M-cell niche: insights from mouse models on how microfold cells “know” where they are needed - Del Castillo, Diana; Lo, David D. (Frontiers in Immunology, 2024)
Known for their distinct antigen sampling abilities, Microfold cells, or M cells, have been well characterized in the gut and other mucosa including the lungs and nasal-associated lymphoid tissue (NALT). More recently, however, they have been identified in tissues where they were not initially suspected to reside, which raises the question: what external and internal factors dictate diXerentiation toward this specific role? In this discussion, we will focus on murine studies to determine how these cells are identified (e.g. markers, function) and ask the broader question of factors triggering M cell localization and patterning . Then, through the consideration of unconventional M cells which include villous M cells, Type II taste cells, and medullary thymic epithelial M cells (microfold mTECs), we will establish the M cell as not just a player in mucosal immunity, but as a versatile niche cell that adapts to its home tissue. To this end, we will consider the lymphoid structure relationship and apical stimuli to better discuss how the diXering cellular programming and the physical environment within each tissue yields these cells and their unique organization. Thus, by exploring this constellation of M cells, we hope to better understand the multifaceted nature of this cell in its diXerent anatomical locales.